Global positioning system activity profile in male para footballers with cerebral palsy - Goh, Alvin M; Maayah, Fadi; Harms, Craig A; Newton, Robert U; Drinkwater, Eric J (2021)
Objective: To compare training and match loads for CP football athletes in a state-level development program to assess the specificity of training for competition in the para sport.